PENYULUHAN DAN PEMBUATAN PUPUK ORGANIK DI DUSUN DUNGTILENG DESA SOMONGARI, KECAMATAN KALIGESING, KABUPATEN PURWOREJO, PROVINSI JAWA TENGAH - Ali, Mahrus (AJIE (Asian Journal of Innovation and Entrepreneurship), 2015)
Farmers in dusun Dungtileng, Somongari village, district of Kaligesing, Purworejo regency, Central Java Provisions, had used organic’s fertilizer. But, they still used the basic material, so the quality is still low. This program was conducted to provide additional insights and teach the farmers of this village cultivate organic fertilizers composed of animal waste, dry leaves, green leaves, fruits decanter of waste, and soil. By improved the quality of organic’s fertilizer, farmers would get many benefits.